FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI MODERASI - Wijaya, Nadya; Dewi, Sofia Prima (Jurnal Paradigma Akuntansi, 2025)
This study aims to find out how the role of company size, profitability, leverage, and liquidity has on company value by using social responsibility as a moderating variable in the consumption sector of non-primary goods listed on the Indonesia Stock Exchange during 2019-2021. The sample was selected by purposive sampling method and there are 17 companies with valid data. The data processing technique uses moderation regression analysis (MRA) assisted by the Eviews 12.0 program and Microsoft Excel 2013. The results of this study indicate that company size does not have a negative effect on firm value, profitability and social responsibility have a positive effect on firm value, leverage and liquidity do not have a positive effect on firm value. Social responsibility can affect the effect of firm size on firm value, social responsibility cannot affect the effect of liquidity on firm value.